Inaktivasi In Situ Pencemaran Kadmium pada Tanah Pertanian Menggunakan Amelioran dan Pupuk pada Dosis Rasional untuk Budidaya Tanaman - Sudadi, Untung; Sabiham, Supiandi; Sutandi, Atang; Saeni, Muchammad Sri (UNIVERSITY OF LAMPUNG, 2008)
Arable soils located in the vicinity of urban and industrial area are considered vulnerable to heavy metals pollution. Chemical inactivation, an in situ remediation method that used inexpensive chemicals to reduce pollutant solubility in polluted soil, was examined on a Cd-spiked arable soil. The study was aimed at to investigate the effectiveness of ameliorants and fertilizers normally recommended for crop cultivation, using tomato as the test plant, from the point of view to reduce soil Cd extractability and plant Cd concentration. A 100-day greenhouse experiment in completely randomized design consisting of three rates of rationale dosage of ameliorants and fertilizers (RDAF) [0, 50, 100%] and four levels of soil Cd spike [0, 10, 20, 40 mg Cd kg-1 soil, using 3CdSO4.8H2O] in triplicate was conducted. The 100% rate of RDAF applied was: 4 ton dolomite ha-1, 30 ton cow dung ha-1, 150 kg N ha-1 (½ Urea + ½ Ammonium Sulfate), 150 kg P2O5 ha-1 (SP-36) and 100 kg K2O ha-1 (KCl). Significant reductions in soil extractable Cd (CdNH4OAc-EDTA) [from 13.35 to 8.77 mg kg-1, 34%] and plant shoots-Cd (Cdps) [from 8.66 to 5.46 μg g-1, 37%] were measured at 100% RDAF treatment as compared to the control soil, indicating the occurrence of an in situ soil Cd inactivation and plant element selective-uptake phenomenon. Multiple regression analysis that incorporating all 36 data pairs resulted in the following equations: (1) soil CdNH4OAc-EDTA = – 0.18 pHH2O + 0.21 PBray#1 + 0.51 organic-C – 0.57 exch.-Mg + 0.65 Cdaqua regia (R2 = 0.76), and (2) Cdps = 0.08 Nps – 0.17 Kps – 0.19 Mgps – 0.24 Pps + 0.27 Sps – 0.41 Caps (R2 = 0.54, 3 outliers removed). These results suggest that a proper amelioration and fertilization program may be prospective to be recommended as a low-cost Cd pollution remediation strategy for arable soils